2004
DOI: 10.1016/j.jbiotec.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Serum- and protein-free media formulations for the Chinese hamster ovary cell line DUKXB11

Abstract: Citation for published item:hr¤ oderD wF nd w tis h kD uF nd priedlD F @PHHRA 9 erumE nd proteinEfree medi formul tions for the ghinese h mster ov ry ell line h u fIIF9D tourn l of iote hnologyFD IHV @QAF ppF PUWEPWPF Further information on publisher's website: httpXGGdxFdoiForgGIHFIHITGjFj iote FPHHQFIPFHHS Publisher's copyright statement:Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 63 publications
1
44
0
Order By: Relevance
“…This effect was cell line specific however, as CHO-K1 grew in insulin-free medium with zinc (marginally slower than with insulin) but the recombinant clone CHO-IFN could not. An alternative strategy to remove the requirement of insulin was used by Schröder et al (2004). By weaning CHO-DU-KXB11 cells from SFM with reducing insulin concentrations, a PFM was generated.…”
Section: Insulinsupporting
confidence: 81%
“…This effect was cell line specific however, as CHO-K1 grew in insulin-free medium with zinc (marginally slower than with insulin) but the recombinant clone CHO-IFN could not. An alternative strategy to remove the requirement of insulin was used by Schröder et al (2004). By weaning CHO-DU-KXB11 cells from SFM with reducing insulin concentrations, a PFM was generated.…”
Section: Insulinsupporting
confidence: 81%
“…As the shear protective effect of PF-68 has been reported to be proportional to its concentration (Ma et al, 2004;Zhang et al, 1992), it is important to know if this uptake phenomenon can significantly affect the Pluronic content in the culture medium. For CHO cells, a 0.2% (w/v) PF-68 concentration is commonly used (Keane et al, 2003;Schroder et al, 2004) and we showed that the presence of cells only slightly affects this concentration. At 0.2% (w/v) with 4 Â 10 6 cells/mL, only a 2.4% decrease of the initial concentration was observed, after 18 h. At the end of a classical bioreactor culture, cell densities can reach up to 10 Â 10 6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Each Pluronic fits for a specific application, from drug solubilization to bioprocess applications. For instance, Pluronic F-68 (PF-68, (EO) 75 -(PO) 30 -(EO) 75 ) is used as a shear protective agent which limits cell death in mechanically agitated gas-sparged bioreactors (Murhammer and Goochee, 1990) and is particularly useful in serum-free medium culture (Keane et al, 2003;Schroder et al, 2004). The protective effect of PF-68 has been demonstrated for suspension culture of mammalian cells (Jordan et al, 1994;Ramirez and Mutharasan, 1990;Zhang et al, 1992), insect cells (Goldblum et al, 1990;Murhammer and Goochee, 1990), and plant cells (Sowana et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For decades, animal-derived serum has been an essential component of mammalian cell culture media (Hu and Aunins, 1997;Schroder et al, 2004). However, a number of issues associated with the use of serum make it preferable to propagate cells in serum-free media (SFM) (Schroder et al, 2004;Sinacore et al, 2000).…”
Section: Introductionmentioning
confidence: 99%